Human rights and the environment: linkages in the Nigerian context (2013)
The legal protection of the environment has increasingly become imperative in view of the importance of a safe, clean and secure environment to the enjoyment of other human rights. Human activities like agriculture, lumbering, manufacturing and worse of all, oil pollution have impacted negatively on the environment, leading to ozone layer depletion, global warming, desertification, erosion, deforestation and environmental pollution in many societies, including Nigeria. International environmental law and human rights law have intertwined objectives and ultimately strive to produce better conditions of life on earth. Both seek to tackle universal challenges that must often be solved at the same time at the individual and global level. Environmental law seeks to protect both nature for itself, and for the benefit of humankind at all levels. It has broadly been confined to regulating inter-state relations and lately, the behaviour of some economic actors such as oil exploiting multinational companies in the Niger Delta of Nigeria. The article examined the linkages between human rights and the environment, as the life and the personal integrity of each human being depends on protecting the environment as the resource base for all life. It reviewed the challenge of locus standi in environmental litigation and the implications of section 6(6)(6)(b) of the 1999 constitution of Nigeria. Against the background that the right to a healthy environment is a fundamental part of the right to life and to personal integrity, it examined instances of violations of human right through the violation of the environment and made recommendations including making the right to a healthy environment a justiciable right to obliterate the problem of locus standi in environmental right litigations.